Relation of PTEN and Ki67 expression with prognosis in gastrointestinal stromal tumors (Annals of Medical Research, 2021)
Aim: The purpose of the present study of ours was to examine the relation of Ki67 and PTEN expression with the prognosis in the pathologies of patients who undergo gastrointestinal stromal tumor surgery in our clinic. Gastrointestinal stromal tumors; In addition to being small incidental tumors; can be tumors with large size and malignant behavior. For this reason, the relation of a great number of macroscopic and microscopic parameters with prognosis was examined. The diameter, location and mitotic index of the tumor rank the first among these parameters; however, several pathological parameters like PTEN and Ki67 expression are also important.Material and Methods: The present study was conducted between January 2005 and April 2015 with patients diagnosed with gastrointestinal stromal tumors. The demographic data (age and gender), tumor localizations, tumor sizes, mitotic activities, prognostic risk classification, follow-up times, PTEN expressions, Ki67 proliferation indices, relapse and metastasis status, andsurvival data of the patients were examined retrospectively.Results: A total of 76 patients were included in the present study. A total of 33 (43.4%) of the participants were women, and the average age was 59.7±11.7 years. The relations of PTEN with risk scores (p=0.330), tumor diameter (p=0.360), location (p=0.169), and mitosis count (p=0.579) were not significant. The relation of PTEN staining rate with relapse (p=0.832), metastasis (p=0.626) and survival (p=0.069) was not found to be statistically significant. The relation of Ki67 expression with risk scoring (p=0.018) and mitosis count (p=0.003) was significant. Although the relation between Ki67 and relapse (p=0.019) and metastasis (p=0.003) was significant, the relation between survival (p=0.655) was not significant at a statistical level.Conclusion: The Ki67 expression was a prognosis-indicating index for relapse and metastasis when the baseline value was taken as 5%; however, no relation was detected between PTEN expression and prognosis.